Delirium as an Adverse Reaction to BNT162b2 mRNA Vaccine from Pfizer Inc., and BioNTech - Lilia M. Sierra Galan; Raquel Cohen Shaooli (APIK Journal of Internal Medicine)
The spike-protein severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine has developed different adverse reactions. Still, delirium has not been reported in a low-risk patient, and it is important to consider it and recognize it as a possibility in all severity risk patients. We present a 76-year-old male patient who developed delirium after receiving the second dose of the BNT162b2 mRNA vaccine from Pfizer Inc. and BioNTech®. We theorize about the potential pathophysiology mechanisms involved.